2020
DOI: 10.3390/diagnostics10060419
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BDNF as a Biomarker for Impulsivity in a Psychiatric Population

Abstract: Impulsivity is an important risk factor for suicide and therefore, identifying biomarkers associated with impulsivity could be important in evaluating psychiatric patients. Currently, assessment of impulsivity is based solely on clinical evaluation. In this study, brain-derived neurotrophic factor (BDNF), a nerve growth factor, was evaluated as a potential biomarker for impulsivity. We hypothesize that elevated BDNF may result in aberrantly high neurobiological activation, promoting impulsive behaviours. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Still, these three polymorphisms have been shown to significantly impact various neuropsychological and psychopathological dimensions among various disorders. Second, it is possible that a modulating effect of the three SNPs studied may have been hidden by the relatively small sample size employed in our study; however, the numerosity of our sample was comparable to the majority of other studies with similar design [26,52,107]. Third, the two groups had significant differences in terms of sociodemographic variables; however, although the mixed regression models accounted for these differences, an effect on our findings cannot be completely ruled out.…”
Section: Httlpr X Gender Interaction Effect On Impulsivity Measuresmentioning
confidence: 55%
“…Still, these three polymorphisms have been shown to significantly impact various neuropsychological and psychopathological dimensions among various disorders. Second, it is possible that a modulating effect of the three SNPs studied may have been hidden by the relatively small sample size employed in our study; however, the numerosity of our sample was comparable to the majority of other studies with similar design [26,52,107]. Third, the two groups had significant differences in terms of sociodemographic variables; however, although the mixed regression models accounted for these differences, an effect on our findings cannot be completely ruled out.…”
Section: Httlpr X Gender Interaction Effect On Impulsivity Measuresmentioning
confidence: 55%
“…In another longitudinal study, increasing serum BDNF levels by pharmacological treatment improved depressive symptoms in patients with schizophrenia (21). There is a correlation between BDNF and impulsive behavior in patients with psychiatric disorders, and some studies have suggested the possibility of using it as a biomarker (22). PI3K, an important kinase of inositol and phosphoinositide, regulates cell growth and migration.…”
Section: Introductionmentioning
confidence: 99%